Practical training report: Miri Resident Office / Lovelyn Leni Edward - Edward, Lovelyn Leni (University Technology MARA Sarawak, 2015)
Miri division is located on the north Sarawak which abutted between Brunei Darulsalam and east Kalimantan Indonesia. Before the year 1941, Sarawak was under the rule of Brunei’s Malay Sultanate. Due to the unstabilize politics and the chaos, it leads to the intervene of James Brooke. During the rule of Charles Brooke, he had appointed one Resident in each division to help him to govern the region. In 1883, Brunei Sultanate had surrendered the division of Bintulu and Baram to Charles Brooke. In 1945 up until 1963, state of Sarawak was under the rule of British colony and it was separated into five divisions. The fourth division of Sarawak at that time consist of Miri Division, Baram Division and Bintulu Division. During the year of 1979, Bintulu Division had been upgraded to one new administration. Currently, Miri has the broadness of 26,777 km2 with 307,782 of citizens. Division of Miri was divided into two division which is : a. Miri Division (included sub-division of Sibuti and Niah) b. Marudi Division (included sub-division of Bakong and Long Lama). The administration of Miri covered the Residen Office Miri, District Office and Sub-District Office which : a. Miri Residen Office govern the entire region in Miri Division which headed by Residen. b. Miri District Office which govern the district of Miri and lead by District Officer. For sub-district which consists of Sibuti and Niad will be lead by District Officer and Sarawak Administrative Officer. c. Marudi District Office which governs the region of Marudi will be lead by District Officer. For sub-district in Marudi which is Bakong and Long Lama will be lead by Sarawak Administrative Officer